Recent developments in the chemistry of bicyclic 6-6 systems: Chemistry of pyrido[1, 2-c]pyrimidines. Issue 18 (16th September 2016) - Elattar, Khaled M.; Rabie, Ramy; Hammouda, Mohamed M.
ABSTRACT: The present review provides a study on the structural features, reactions, and synthetic methodologies of pyrido[1, 2- c ]pyrimidines. The maximum deviation from the mean plane of the pyridopyrimidine skeleton of 4-(pyridin-2-yl)-1 H -pyrido[1, 2- c ]pyrimidine-1, 3(2 H )-dione indicated a reasonably planar system. The aim of this review is to give an overview of the diverse methodologies that have been reported on the chemistry of pyrido[1, 2- c ]pyrimidines. The different synthetic routes have been grouped according to the way the pyrido[1, 2- c ]pyrimidine moiety has been created. Thus, pyrido[1, 2- c ]pyrimidine compounds were obtained by the formation of one bondα to the bridgehead nitrogen atom [6+0(β )] and formation of two bonds from ([3+3], [4+2], and [5+1]) atom fragments. The mechanistic pathways of the reactions are discussed. GRAPHICAL ABSTRACT: